Globalizing Chinese Brands: Perspectives and Strategy Implications - Khera, Inder P. (Indian Journal of Marketing, 2011)
The purpose of the paper is to discuss the reasons why China, which has become the world’s manufacturing powerhouse, has not had a corresponding success in marketing its own brands internationally. The paper discusses the phenomenon of branding in China, brand consciousness and brand preferences among Chinese customers, success of local and foreign brands in the Chinese market, and efforts by Chinese companies and government to promote the brand-building activity within China and overseas. Managerial, competitive, and other reasons for the lack of success in building brand equity by Chinese firms are discussed and roadblocks to success in foreign, especially First World, market are examined. The paper concludes with several suggestions that could be helpful to Chinese firms to promote their branded products in world markets.